BANK SAMPAH CANGKIR HIJAU: GERAKAN EKONOMI KREATIF MELALUI KERAJINAN SAMPAH UPAYA MENJAGA LINGKUNGAN HIDUP DI KOTA METRO LAMPUNG - Bambang Suhada (Postgraduate State Islamic Institute (IAIN) Metro, 2016)
This research explains about the function of “bank sampah cangkir hijau” in conducting creative economy movement through garbage craft as an action to save the environment in Metro City, Lampung. “Bank Sampah” creates by Lecturer and Students of STAIN Jurai Siwo Metro purposed to save the environment by managing the rubbish into creative craft. “Kresbag” is a cloth bag which has interesting pack and it help people to be aware to bring their own bag shopping. “Bank Sampah” which manages by students helps them to pay their study independently. This empowerment use ethnographic approach to answer the submitted questions. This research applied Pierre Bourdieu's theory of Intellectual Collective which has meaning as a diverse movement of multidisciplinary knowledge and profession to make social change.